Bacterial Glycosyltransferases: Challenges and Opportunities of a Highly Diverse Enzyme Class Toward Tailoring Natural Products - Schmid, Jochen; Heider, Dominik; Wendel, Norma J.; Sperl, Nadine; Sieber, Volker (Frontiers in Microbiology, 2016)
The enzyme subclass of glycosyltransferases (EC 2.4) currently comprises 97 families as specified by CAZy classification. One of their important roles is in the biosynthesis of disaccharides, oligosaccharides and polysaccharides by catalyzing the transfer of sugar moieties from activated donor molecules to other sugar molecules. In addition glycosyltransferases also catalyze the transfer of sugar moieties onto aglycons, which is of great relevance for the synthesis of many high value natural products. Bacterial glycosyltransferases show a higher sequence similarity in comparison to mammalian ones. Even when most glycosyltransferases are poorly explored, state of the art technologies, such as protein engineering, domain swapping or computational analysis strongly enhance our understanding and utilization of these very promising classes of proteins. This perspective article will focus on bacterial glycosyltransferases, especially on classification, screening and engineering strategies to alter substrate specificity. The future development in these fields as well as obstacles and challenges will be highlighted and discussed.